Alkylamino derivatives of pyrazinamide: synthesis and antimycobacterial evaluation - Servusová, Barbora; Paterová, Pavla; Mandíková, Jana; Kubíček, Vladimír; Kučera, Radim; Kuneš, Jiří; Doležal, Martin; Zitko, Jan (Bioorganic & medicinal chemistry letters, 2014)
A series of pyrazinamide derivatives with alkylamino substitution was designed, synthesized and tested for their ability to inhibit the growth of selected mycobacterial, bacterial and fungal strains. The target structures were prepared from the corresponding 5-chloro (1) or 6-chloropyrazine-2-carboxamide (2) by nucleophilic substitution of chlorine by various non-aromatic amines (alkylamines). To determine the influence of alkyl substitution, corresponding amino derivatives (1a, 2a) and compounds with phenylalkylamino substitution were prepared. Some of the compounds exerted antimycobacterial activity against Mycobacterium tuberculosis H37Rv significantly better than standard pyrazinamide and corresponding starting compounds (1 and 2). Basic structure-activity relationships are presented. Only weak antibacterial and no antifungal activity was detected.
Keywords: Antifungal Agents; pyrazinamid; preklinické hodnocení léčiv; Pyrazinamide; buňky Hep G2; Antitubercular Agents; antibakteriální látky; Crystallography; Microbial Sensitivity Tests; antifungální látky; antituberkulotika; Antimycobacterial activity; lidé; Cytotoxicity; krystalografie; Anti-Bacterial Agents; Humans; Drug Evaluation, Preclinical; mikrobiální testy citlivosti; 6-Chloropyrazine-2-carboxamide; Hep G2 Cells; Alkylamines; 5-Chloropyrazine-2-carboxamide; Mycobacterium tuberculosis